On C^*-algebras associated to actions of discrete subgroups of SL(2,R) on the punctured plane - Bassi, Jacopo (MATHEMATICA SCANDINAVICA, 2020)
Dynamical conditions that guarantee stability for discrete transformation group C^*-algebras are determined. The results are applied to the case of some discrete subgroups of SL (2,R ) acting on the punctured plane by means of matrix multiplication of vectors. In the case of cocompact subgroups, further properties of such crossed products are deduced from properties of the C^*-algebra associated to the horocycle flow on the corresponding compact homogeneous space of SL (2,R ).